1998
DOI: 10.1016/s0895-7061(98)00054-5
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Calcium/Creatinine Ratio as a Predictor of Preeclampsia

Abstract: Hypocalciuria has been associated with preeclampsia (gestational hypertension with proteinuria or other maternal organ dysfunction) but not usually with pure gestational hypertension or normal pregnancy. We hypothesized that hypocalciuria would be a marker of emerging preeclampsia in women presenting with gestational hypertension who later developed preeclampsia. Eighty-one women with de novo hypertension in the second half of pregnancy (n = 81) were enrolled prospectively. At first assessment, calcium/creatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 12 publications
1
11
1
Order By: Relevance
“…In my study, however, such of women were excluded and this might explain the difference between present findings and that of Ozcan and Kaleli (1995). Saudan et al (1998) conducted a similar study but obtained a different cut-off point, 0.1 instead of present 0.225, which yielded a lower sensitivity and specificity than the present study (75% and 65%, respectively). 17 The present study is almost similar to that of Tkazerooni 20 and Hamze-Nejadi, (2003) where cut of point was 0.229, sensitivity 75% and specificity 77.7%.…”
Section: Discussioncontrasting
confidence: 70%
“…In my study, however, such of women were excluded and this might explain the difference between present findings and that of Ozcan and Kaleli (1995). Saudan et al (1998) conducted a similar study but obtained a different cut-off point, 0.1 instead of present 0.225, which yielded a lower sensitivity and specificity than the present study (75% and 65%, respectively). 17 The present study is almost similar to that of Tkazerooni 20 and Hamze-Nejadi, (2003) where cut of point was 0.229, sensitivity 75% and specificity 77.7%.…”
Section: Discussioncontrasting
confidence: 70%
“…Significantly higher serum Uric acid concentration was observed in preeclampsia patients (6.76± 1.99 vs 3.86± .75, p<0.01). Previous Research works by Saudan et al 22 and Qublan et al 9 had similar results indicating possibilities of serum uric acid to be considered as an important factor for preeclampsia. Regarding urinary biochemical in the present study we estimated spot urinary calcium concentration (mg/100ml), spot urinary creatinine concentration (mg/100ml) and spot urinary protein concentration (mg/100ml).…”
Section: Resultssupporting
confidence: 53%
“…Regarding the demographic variables, mean age ± SD of the preeclampsia and normal pregnant group were 9 and Soudan et al 22 . Regarding parity 44% patients of preeclampsia and 37% normal pregnant were nullipara; but 36% of both groups were primipara.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Ozcan et al 5 who investigated the predictive value of decreasing calcium to creatinine ratio in a spot urine sample as early as in 1995 reported that it might be an effective marker for preeclampsia. Saudan 6 , have reported a sensitivity of only 68% and specificity of 70% and Izumi et al 7 found that it had limited value in prediction of preeclampsia, but the threshold value used was 0.10 by the former and Izumi et al carried out the test in early pregnancy, at less than or equal to 12 weeks of gestation. Kazeroomi 8 evaluating between 20-24 weeks of gestation and Kar et al 9 evaluating the predictive value of CCR at less than or equal to 0.04 between 20-34 weeks of gestation (similar to our study), have reported that it was a satisfactory test for prediction of preeclampsia and could be an effective method for screening asymptomatic women for preeclampsia.…”
Section: Discussionmentioning
confidence: 99%